The Effect of Sunkist Orange Proportions with Banana and Types of Stabilizing Materials on the Characteristics of Banana Jam - Mega Ari Sovani; Lukman Hudi (jurnal makanan tropis dan teknologi agroindustri, 2021)
This study aims to determine the effect of the proportion of sunkist oranges with candi bananas and the type of stabilizer on the characteristics of banana jam. The research was carried out at the Muhammadiyah University Sidoarjo Laboratory from January to March 2019. The design used was a factorial randomized block design. Factor 1 is the proportion of sunkist oranges (js) with candi bananas (pc), namely S1 (js15%: pc85%), S2 (js30%: pc70%), S3 (js45%: pc55%), Factor 2 types of stabilizers, namely P1 ( CMC 0,5%), P2 (carrageenan 0,5%), P3 (pectin 0,5%). Statistical analysis using analysis of variance and further test BNJ test 5%. The results showed that there was no significant interaction between the proportion of sunkist oranges and candi bananas and the type of stabilizer, but it had a significant effect on organoleptic color, texture, taste, and spreadability of banana jam. The stabilizer type treatment had a significant effect on the water content of banana jam, while the proportion of sunkist oranges and candi bananas had a significant effect on vitamin C content, pH, and banana jam yellowness values. The results of the calculation of the best treatment are the proportion of sunkist oranges with candi bananas (45%:55%) and carrageenan stabilizer 0,5% which shows moisture content 16,99%, ash content 0,27%, vitamin C content 4,11mg/100ml, pH 3,96, Color L* 49,25, a* -1,05, b* 28,73, and organoleptic color 5,40, aroma 4,37, texture 4,60, taste 4,37, and spreadability 4,77.